Politics, Peace and Predestination - Hollingworth, Miles (Editorial Uniagustiniana, 2019)
This chapter is intended to show that Augustine's political philosophy can speak with a radical voice into situations of extreme ideological conflict today-most especially where these involve gross disparities of wealth. The key to allowing this radical Augustinian voice to speak, is first to spend a good deal of time identifying the exact coordinates into which it can speak. These coordinates may surprise us, and they are the chief innovation of this chapter. For convenience sake, I lever the search for these coordinates against the general idea of radical socialism, understood as a philosophy of history. The result of this approach is that it eventually brings us out on Augustine's doctrine of predestination; and allows us to begin to see it as the practical touchstone of a new radical Augustinianism. This new radicalism does not need to make use of the device that liberation theology made use of, viz., a preferential option for the poor. Instead, it moves beyond all such class distinctions to direct itself against the very dynamics which have shaped political logic in the West since Plato.